2023
DOI: 10.3389/fped.2022.1005947
|View full text |Cite
|
Sign up to set email alerts
|

Does physiological-based cord clamping improve cerebral tissue oxygenation and perfusion in healthy term neonates? – A randomized controlled trial

Abstract: ObjectivesTo evaluate cerebral tissue oxygenation index (cTOI) during neonatal transition in a group of healthy full-term neonates receiving either a physiological-based approach of deferred cord clamping (CC) after the onset of stable regular breathing (PBCC group) or a standard approach of time-based CC < 1 min (control group). Secondary aim was to evaluate changes in cerebral blood volume (ΔCBV), peripheral arterial oxygen saturation (SpO2) and heart rate (HR) in those neonates.Materials and MethodsW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 51 publications
3
0
0
Order By: Relevance
“…This similarity of global parameters is in accord with the few available clinical reports, wherein little or no difference was present between PBCC (i.e. DCC preceded by an extended 4-5 min period of initial ventilation) and conventional DCC with 1 min of prior ventilation, with respect to changes in heart rate and peripheral arterial oxygenation (via pulse oximetry) in term infants (Schwaberger et al, 2022) or short-term neonatal outcomes in very preterm (<32 weeks gestation) infants (Knol et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…This similarity of global parameters is in accord with the few available clinical reports, wherein little or no difference was present between PBCC (i.e. DCC preceded by an extended 4-5 min period of initial ventilation) and conventional DCC with 1 min of prior ventilation, with respect to changes in heart rate and peripheral arterial oxygenation (via pulse oximetry) in term infants (Schwaberger et al, 2022) or short-term neonatal outcomes in very preterm (<32 weeks gestation) infants (Knol et al, 2020).…”
Section: Discussionsupporting
confidence: 87%
“…4,5 With regards to cerebral oxygenation in the delivery room, a recent RCT found no differences between PBCC and ECC in vaginally-born, full-term neonates not needing resuscitation. 28 Our findings were similar in a population that received resuscitation and included caesarean births. In contrast, Katheria et al found that at 12 h after birth, cerebral oxygen saturation and BP were higher among term infants at risk of needing resuscitation who were randomised to UCC at 5 min versus within 1 min after birth.…”
Section: Discussionsupporting
confidence: 76%
“…With regards to cerebral oxygenation in the delivery room, a recent RCT found no differences between PBCC and ECC in vaginally-born, full-term neonates not needing resuscitation. 27 Our findings were similar in a population that received resuscitation and included caesarean births. In contrast, Katheria et al found that at 12 hours after birth, cerebral oxygen saturation and BP were higher among term infants at risk of needing resuscitation who were randomised to UCC at 5 min versus within 1 min after birth.…”
Section: Discussionsupporting
confidence: 76%